Pemanfaatan Media Sosial Sebagai Sarana Edukasi Literasi Bagi Siswa Sekolah Dasar Negeri 1 Serang: Pengabdian - Anton Nasrullah; Mira Marlina; Sarah Caesarani; Widya Dwiyanti; Mimih Aminah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Social media use among school youth is increasing, but it is often used without adequate understanding of its educational and literary value. This situation gives rise to various problems such as the spread of false information, digital addiction, and low media literacy skills. This community service activity aims to improve the understanding and skills of school youth in utilizing social media positively as a means of education and digital literacy. Implementation methods include outreach, interactive training, group discussions, and mentoring in creating engaging and informative educational content on social media platforms such as Instagram, TikTok, and YouTube. The results of the activity indicate an increase in participants' knowledge and awareness of the importance of digital literacy, internet ethics, and skills in creating useful content. The impact is evident in changes in adolescents' attitudes toward using social media wisely and productively to support learning and share positive information. In conclusion, appropriately directed use of social media can be an effective tool for improving literacy and education among school youth, while simultaneously developing a generation of intelligent, creative, and responsible young people in the digital era.